Social enterprises in Asia : a new legal form / Ernest Lim, National University of Singapore. - Lim, Ernest, 1977- (International corporate law and financial market regulation., 2023)
Social enterprises are regarded as a vital solution to the pressing problem of socio-economic inequality and play a crucial role in the delivery of public goods and services. Ernest Lim argues that social enterprises in four leading Asian jurisdictions - India, Hong Kong, Singapore and Malaysia - should have a new legal form. This entails advancing a nuanced and comprehensive framework consisting of five criteria: (1) corporate purpose; (2) directors' duties; (3) decision-making powers; (4) reporting, impact measurement and certification; and (5) distribution of dividends, assets, and tax benefits. This invaluable work demonstrates that the existing legal forms in common law Asia, the UK and the US do not properly address the various conflicts of interest affecting social enterprises. An essential read for those interested in understanding and evaluating the laws and regulations on social enterprises, as well as designing and implementing creative ones to protect and promote these important businesses.